SEMANTIC ANALYSIS OF PROVERBS WITH THE SOMATIC COMPONENT “HEAD” (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article presents a comparative analysis of proverbs that incorporate the somatic component “head” in both English and Uzbek languages. The study delves into the semantic nuances and cultural contexts of these proverbs, shedding light on their shared themes and language-specific expressions. Through a detailed examination of well-known proverbs in both languages, the article highlights common lessons related to cooperation, composure, rationality, understanding complexity, and accountability. It also underscores the rich tapestry of idiomatic expressions and linguistic variations that reflect the unique cultural values and linguistic nuances of each language. This cross-linguistic exploration of somatic proverbs provides valuable insights into the universal human experiences and the diverse ways in which different cultures convey similar wisdom through metaphorical language. Researchers, linguists, and anyone interested in cross-cultural communication and linguistic analysis will find this article a valuable resource for understanding the depth of meaning embedded in these idiomatic expressions.